Interactive Learning Media Using Articulate Storyline 3 in Minang Kabau Culture Cours in Informastic And Computer Engineering Education IAIN Bukit Tinggi - Ahmad Baqi (Pascasarjana UIN Sumatera Utara, 2022)
This research is motivated by learning Minangkabau Culture which in general the material is only in the form of delivering papers with the lecture method. In its delivery, lecturers use minimal learning media in class and the use of adequate technological facilities is still underutilized by lecturers so that boring learning methods have an impact on student interest in learning to be low. This study uses the Research And Development (R&D) method using the 4D version approach, namely Define, Design, Develop, and Disseminate. using Luther Sutopo's multimedia development model which consists of 6 stages, namely concept, design, collecting material, assembly, testing and distribution. The product test used in this study is the validity test using the Aiken's